2007
DOI: 10.1590/s1415-47572007000100020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of high inbreeding in a population of the endangered giant anteater, Myrmecophaga tridactyla (Myrmecophagidae), from Emas National Park, Brazil

Abstract: We report the genetic structure, relatedness and mating structure of a population of the endangered giant anteater Myrmecophaga tridactyla Linnaeus, 1758 in the Emas National Park, Brazil, based on variability at five microsatellite loci. Additionally, we addressed the hypothesis that the M. tridactyla population studied has low levels of polymorphism and high levels of inbreeding and relatedness and that animals with overlapping home range are highly related. All five microsatellite loci displayed low levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 51 publications
0
30
0
4
Order By: Relevance
“…For example, they can be used in making estimates of inbreeding (e.g. Collevatti et al, 2007;Blackmore & Heinsohn, 2008;Richard et al, 2009), heritability (e.g. Garant & Kruuk, 2005;Charmantier et al, 2006) and gene flow (Zeyl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they can be used in making estimates of inbreeding (e.g. Collevatti et al, 2007;Blackmore & Heinsohn, 2008;Richard et al, 2009), heritability (e.g. Garant & Kruuk, 2005;Charmantier et al, 2006) and gene flow (Zeyl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…obs., Merritt (2008). Such periodic concentrations of population associated with increased mortality may also contribute to the genetic bottlenecking described by (Collevatti et al 2007) and a source of error in population estimates.…”
Section: Page 10mentioning
confidence: 99%
“…Until the fourth month the maximum distance had increased to about 20m, with about 50 minutes per week spent at this distance, increasing to more than three hours by nine months of age. Collevatti et al (2007) reported high levels of inbreeding at PN Emas, Brazil, noting that animals with overlapping range were highly-related. They noted that the amount of inbreeding may have been an indirect result of catastrophic fires in the reserve in 1994, which left a population of just 43 animals, though they may just as likely be a result of the biology of the species.…”
mentioning
confidence: 99%
“…Segundo Collevatti et al (2007), o tamanduá bandeira é a maior espécie de tamanduá do mundo e está amplamente distribuído na América Central e do Sul, apesar de sua ampla abrangência ter sido extinta em muitas áreas da sua original distribuição. Medri e Mourão (2005) afirmam que a distribuição dos tamanduás ocorre a partir do sul da Guatemala até o norte da Argentina, abarcando uma variedade de habitats nas altitudes baixas e podendo atingir altas densidades, onde seu alimento, que consiste principalmente de formigas e cupins, é abundante.…”
Section: Introductionunclassified